Penerapan Pendekatan SETS (Science, Environment, Technology, and Society) untuk Meningkatkan Hasil Belajar Biologi Siswa - Rafael Riwu; I Wayan Budiyasa; I Gusti Ayu Rai (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
The study aims to determine the increase in biology learning outcomes of students of class X IPA-7 even semester SMA N 2 Denpasar academic year 2017/2018 through the application of the SETS (Science, Environment Technique and Society) approach. This type of research is classroom action research (CAR) conducted in two cycles. Subjects were 36 students. The research data was collected through observation using multiple choice instruments. Data were analyzed descriptively, in the first cycle, the average learning outcomes 74.77 increased 5.84 to 80.61 and the second cycle increased 6.39 to 87. Absorption in the first cycle: 74.77% increased 5.84% to 80.61% and the second cycle increased 6.39% to 87%. Classical learning completeness in the first cycle 58.33% increased 16.67% to 75% (under KKM: 85%), then continued to cycle II. In the second cycle, classical completeness was obtained by increasing 16.66% to 91.66%. It was concluded that the application of the SETS approach was able to improve the biology learning outcomes of students of class X IPA-7 in the even semester of SMA 2 Denpasar in the academic year 2017/2018.